2016
DOI: 10.1001/jamaophthalmol.2015.5332
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Prevalence of Diabetic Macular Edema Based on Monocular Fundus Photography vs Optical Coherence Tomography

Abstract: IMPORTANCE Diagnosing diabetic macular edema (DME) from monocular fundus photography vs optical coherence tomography (OCT) central subfield thickness (CST) can yield different prevalence rates for DME. Epidemiologic studies and telemedicine screening typically use monocular fundus photography, while treatment of DME uses OCT CST. OBJECTIVE To compare DME prevalence from monocular fundus photography and OCT. DESIGN, SETTING, AND PARTICIPANTS Retrospective cross-sectional study of DME grading based on monocular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
78
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 20 publications
0
78
0
Order By: Relevance
“…In addition, it is also possible to rule out CSMO at an early stage which may reduce concerns of the patients (Mackenzie et al 2011;Wong et al 2017). In a comparative study of 246 eyes, Wang et al (2016) concluded that there was a considerable inconsistency in the detection of DMO and CSMO when fundus photography and OCT were compared. This led to a false-positive rate of referral for CSMO of 86.6% in a screening setup without OCT.…”
Section: Indications To Include Optical Coherence Tomography (Oct)mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it is also possible to rule out CSMO at an early stage which may reduce concerns of the patients (Mackenzie et al 2011;Wong et al 2017). In a comparative study of 246 eyes, Wang et al (2016) concluded that there was a considerable inconsistency in the detection of DMO and CSMO when fundus photography and OCT were compared. This led to a false-positive rate of referral for CSMO of 86.6% in a screening setup without OCT.…”
Section: Indications To Include Optical Coherence Tomography (Oct)mentioning
confidence: 99%
“…1 Supplementary macular OCT should be performed if possible in the case of suspected or overt CSMO, or clinically significant loss of vision (at least two Snellen lines) which cannot be explained by concurrent disease (Virgili et al 2007;Wang et al 2016). In such cases, it is possible to qualify the suspicion of CSMO, thereby optimizing referral for further examinations and/or treatment.…”
Section: Indications To Include Optical Coherence Tomography (Oct)mentioning
confidence: 99%
See 1 more Smart Citation
“…DME, but not DR per se, is nowadays the main cause of vision loss in patients with diabetes 7 . Although estimations may diff er upon the diagnostics used 8 , studies revealed up to 21 million DME and 28 million vision threatening DR 7 . Diabetic macular edema is a special form of diabetic retinopathy, a highly specifi c microvascular complication of diabetes on the eyes.…”
Section: Introductionmentioning
confidence: 99%
“…In the setting of diabetic retinopathy, this “store-and-forward” paradigm has been validated against clinical examination and as well as the research gold standard 7-field Early Treatment Diabetic Retinopathy Study images 1 ; it has been demonstrated that remotely acquired images can allow clinicians to reach the same diagnosis and management plan as these more traditional methods. While there have been questions about the possible role for ultrawidefield imaging 1 and optical coherence tomography in ocular telehealth paradigms, 2 monoscopic photographic imaging has become the foundation of large diabetic retinopathy screening programs. 3 …”
mentioning
confidence: 99%